Aku dan Dia, Cantik Mana? Perbandingan Sosial, Body Dissatisfaction dan Objektivikasi Diri - Suprapto, Maria Helena; Aditomo, Anindito (ANIMA Indonesian Psychological Journal, 2007)
This study was keen to investigate whether a relation exists between self-objectivication and body dissatisfaction; whether a difference exists in body dissatisfaction as a result of social comparison; and whether self-objectivication level of adolescent girls moderate this affect. An experimental pretest-posttest independent group design was used. Participants (N = 32) were 17 - 22 aged psychology students. Results reveal a correlation between self-objectivication and body dissatisfaction. Nonetheles, there is no influence of social comparison towards body dissatisfaction, also no such influence exists towards body dissatisfaction moderated by self-objectivication level. The effectivity of treatment, partisipants’ personality are discussed, along with self-improvement and self-enhancement motives in conducting social comparison. Penelitian ini bertujuan menemukan adanya hubungan antara objektivikasi diri dan body dissatisfaction, apakah ada perbedaan body dissatisfaction yang diakibatkan oleh perbandingan sosial, dan apakah tingkat objektivikasi diri pada remaja putri memoderasi pengaruh tersebut. Penelitian ini menggunakan metode eksperimental dengan desain “pre-test post-test independent group design”. Partisipan adalah mahasiswi berusia 17-22 tahun. Hasil penelitian ini yaitu ada korelasi objektivikasi diri dengan body dissatisfaction. Namun, tidak ada pengaruh perbandingan sosial terhadap body dissatisfaction, juga tidak ada pengaruh perbandingan sosial terhadap body dissatisfaction yang dimoderatori tingkat objektivikasi diri. Hal ini disebabkan kurang efektifnya perlakuan, faktor kematangan pribadi partisipan, dan belum mempertimbangkan motif self-improvement dan self- enhancement dalam melakukan perbandingan sosial.